Reversing graph transformations - Sobocinski, Pawel (Electronic Communications of the EASST, 2007)
In recent work with Vincent Danos and Jean Krivine the author introduced a general framework for backtracking in concurrent formalisms, thus allowing modelling of situations where deadlock can arise without the necessity of explicitly encoding the often involved backtracking mechanisms. Here we shall discuss how the framework can be applied to the well-known formalism of double-pushout graph transformation.